Sustainable and equitable agricultural mechanization? A gendered perspective on maize shelling - Fischer, Gundula; Kotu, Bekele Hundie; Mutungi, C. (Cambridge University Press, 2021)
How can agricultural mechanization be accomplished in a sustainable and equitable way? This question has gained increased prominence in mechanization research over the past few years. In this study, we apply the question to mechanized maize shelling in Tanzania as a case in point. Data from a survey with 400 farmers and from semi-structured interviews with 21 key informants are combined for a gender analysis that relies on Kabeer's concept of four institutional sites (household, community, market and government). The findings reveal that although mechanization reduces men's and women's perceived drudgery of shelling, relief depends on gendered patterns of labor allocation and decision-making at the household level. As a result, the transformation of inequitable norms emerges as paramount. Key informants identified additional aspects that would make mechanized shelling more equitable and sustainable, such as mainstreaming gender and mechanization in comprehensive agricultural training, or the sensitization of mechanized input suppliers and manufacturers to farmers' preferences (including gender-sensitive machine design). Concerted efforts in multiple institutional sites are needed to achieve lasting change in respect of equity in mechanization.